Analisis Jenis Rima pada Lagu Kukira Kau Rumah dan Tuhan Sebut Kau Sia Sia Karya Pendarra: Penelitian - Siti Saharia; Maria Ermelinda D. Lering; Robertus Adi Sarjono Owon (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this research is to find out the types of rhymes found in the song Kukira Kau Rumah and Tuhan Sebut Kau Sia – Sia by Pendarra. This descriptive qualitative research is a literature study research through document analysis in the form of arrays from the song Kukira Kau Rumah and Tuhan Sebut Kau Sia – Sia by Pendarra. Data collection techniques in this study are observation techniques, documentation and recording techniques of song lyrics that have rhymes. The data analysis technique used consists of data reduction techniques, data presentation and conclusion drawing. Based on the results of the study, there are five types of rhymes in the song Kukira Kau Rumah and Tuhan Sebut Kau Sia – Sia by Pendarranamely perfect rhyme, alliteration rhyme, middle rhyme, broken rhyme and final rhyme.